PENGISIAN BORANG AKREDITASI STANDAR 3 MENGGUNAKAN MODEL DATA WAREHOUSE (Studi kasus IBI Darmajaya) - Deppi Linda (IIB Darmajaya, 2015)
To support the information which are needed of an organization in making good decision-making processes, are reguired an information infrastructure to store and to process the data. The use of daily operational data as resources kontrabution strategy gives less adequate for the organization. Therefore, the data warehouse is a concept and a combination of technologies that facilitates organizations to manage and to maintain historical data derived from operational systems. Constraints faced is the lack of support systems that support the accreditation forms primarily charging standard form filling 3 on the data and a graduate student and difficult to obtain information related to the trend in the quality of students meach study program from period to period. In completing the accreditation forms using analysis methodology Online Analytical Processing and method development Business Life Cycle, the results of the research needed to support charging accreditation forms mainly form filling standard 3 regarding the data of student and graduate and obtain information related to the number of prospective students, the number of new students at the faculty and the number of graduates who also grouped by type and their cumulative grade point percentages.Keywords: Data Warehouse, Business Life Cycle, Accreditation, Accreditation